Attitudes towards and Beliefs about HIV Testing among Latino Immigrant MSM: A Comparison of Testers and Nontesters - Rosa Solorio; Mark Forehand; Jane Simoni (AIDS Research and Treatment)
Latino immigrant men who have sex with men (MSM) are at risk for HIV and delayed diagnosis. An exploratory study using qualitative interviews that assess the beliefs and attitudes of 54 Latino immigrant MSM in Seattle, Washington, is presented. The goal of this research is to determine whether attitudinal differences exist between participants who had and had not been tested and to use any insight into the development of a media campaign to promote testing. Over one-third of the men have never been tested for HIV. Nontesters are more likely to be men who have sex with men and women, have less knowledge about HIV risks, perceive their sexual behaviors as less risky, and deflect HIV-related stigma. Testers are more likely to be self-identified as being gays. Both groups believe that fear of a positive result is the main barrier to testing. Both groups believe that family members have negative attitudes towards HIV testing and that having Latino staff at HIV testing sites hinders confidentiality. Financial concerns with regard to the cost of testing were also expressed by both groups. Based on these insights, recommended strategies for the development of HIV prevention and testing campaigns are made.